Los centros históricos de Iberoamerica. Políticas Y improvisaciones - DOI: 10.5752/P.2316-1752.2009v16n18/19p321 - Gutiérrez, Ramón (Cadernos de Arquitetura e Urbanismo, 2010)
Abstract This is a review of the policies formulated for the conservation of historical centers of the continent since the second half of the 20 th century. It analyses the criteria for the definition of centers based on the set of “monumental works”, their insertion into the planning, and the passage from punctual reading to the whole set. It focuses on the ideas of a more complex view, so as to include social themes side by side with cultural ones, and of a definition of housing policies to improve the conditions of abandoned or degraded areas. It also considers the role of tourism as a dynamic element and the risks of disregarding the inhabitants in face of major inversions. The review of historical centers in the integrating perspective of the concept of “cultural landscape” empowers the sense of citizenship and assures more efficient policies and actions. Key words : Historical centers; Cultural landscape; Tourism; Social housing.